Great Silk Way as the Eurasian cross-cultural concept (Eurasian Journal of Philology Science and Education, 2016)
The article considers the concept «Great Silk Way» used by travel agencies of Kazakhstan and Central Asia as information basis of an advertizing product. The Great Silk Way as a cultural artifact of history became a concept in languages and culture of the people occupying the territory along all its directions. In Kazakhstan, for example, such language means as Great Silk Way, Zhibek Zholy, Silk Road, Silk Tour, Silk Way are used as verbalization of the name of the concept in polycultural society. The results of the contextual analysis of use of the name of the concept allowed to reveal the content of the concept and to define it as the Eurasian cross-cultural concept. The authors of the article described the content of transformational processes of the cultural component of this concept, gave an assessment to a historical and cultural role of artifact in the development of human civilization, considered cases of appearance of quasi-estimation in the course of naming with the use of the name of the concept or its foreign-language analog.
Keywords: concept; Eurasian concept; cultural component; advertis¬ing text; estimation; quasi-estimation; naming.